2007
DOI: 10.3168/jds.2007-0152
|View full text |Cite
|
Sign up to set email alerts
|

Passive Transfer of Immunoglobulin G and Preweaning Health in Holstein Calves Fed a Commercial Colostrum Replacer

Abstract: The objective of this study was to describe passive transfer of IgG and preweaning health in newborn calves fed a commercially available plasma-derived colostrum replacement (CR) product or maternal colostrum (MC). Twelve commercial Holstein dairy farms enrolled singleton newborn heifer calves to be fed fresh MC (n = 239 calves) or one dose of CR containing 125 g of Ig (n = 218 calves) as the first colostrum feeding. For 7 of these farms that routinely provided a second feeding of 1.9 L of MC to their calves 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 13 publications
9
85
2
4
Order By: Relevance
“…Dairy colostrum has been shown to have a much lower IgG concentration than beef colostrum (Guy et al, 1994). In addition, calves fed colostrum replacer or supplements may have lower serum IgG concentrations than calves fed fresh colostrum, which may be due to lower IgG concentrations per dose of product or insufficient amounts being fed (Quigley et al, 1998;Swan et al, 2007). Furthermore, if these alternatives were not readily available, the resulting time delay may have affected IgG absorption (Godden, 2008).…”
Section: Colostrum Managementmentioning
confidence: 99%
“…Dairy colostrum has been shown to have a much lower IgG concentration than beef colostrum (Guy et al, 1994). In addition, calves fed colostrum replacer or supplements may have lower serum IgG concentrations than calves fed fresh colostrum, which may be due to lower IgG concentrations per dose of product or insufficient amounts being fed (Quigley et al, 1998;Swan et al, 2007). Furthermore, if these alternatives were not readily available, the resulting time delay may have affected IgG absorption (Godden, 2008).…”
Section: Colostrum Managementmentioning
confidence: 99%
“…As with maternal colostrum feeding, the expectation is that recipient calves reach the minimum 1000 mg/dL serum IgG concentration, indicative of a successful transfer of immunity. To date, the CR studies that have focused either on achieving this minimum serum IgG concentration or a serum IgG concentration comparable to calves fed maternal colostrum as outcomes have shown disappointing results (Mee et al, 1996 ;Quigley et al, 2001 ;Smith & Foster, 2007 ;Swan et al, 2007 ) unless higher doses were fed (Quigley et al, 2001 ;Jones et al, 2004 ;Foster et al, 2006 ;Godden et al, 2009a ). These studies provide evidence that, similar to maternal colostrum, calves fed CR products require a minimum 150 -200 -g dose of IgG for successful passive transfer.…”
Section: Colostrummentioning
confidence: 72%
“…Suckling a nipple bottle, using an esophaet al, 1999a ). Whether maternal colostrum, a colostrum replacement (CR), or a combination of CR and supplement product is fed (Quigley et al, 2002 ;Swan et al, 2007 ;Smith & Foster, 2007 ), an adequate immunoglobulin mass must be presented to the calf when absorption effi ciency is optimal. The IgG concentration in colostrum is variable (Pritchett et al, 1994 ;Morin et al, 1997 ;Swan et al, 2007 ;Chigerwe et al, 2008 ).…”
Section: Colostrummentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, Swan et al, (2007) showed that passive transfer of IgG and preweaning health in newborn calves fed a commercially available plasma-derived colostrum replacement (CR) product or maternal colostrum may have had an opportunity against the pathogenic agent. Accordingly, William et al (2014) and Priestley et al (2013) pointed that passive transfer of antibody using colostrum replacement is a good choice because it contains nutrients and high level of IgG.…”
Section: Introductionmentioning
confidence: 99%